Napoleonic Governance and the Integration of Europe
XXV, 261 p. 9 illus.
Keywords: Between 1792 and 1815 Europe was plunged into a period of profound turmoil and transformation. The French Revolution unleashed a torrent of political, social, cultural, and military changes. Napoleon extended them beyond the country’s frontiers. The ensuing struggle was immense in its scale and intensity. Never before had European states resorted to a mobilization of civilian and military resources as comprehensive as during this period. This book explores the practical and philosophical challenges that Napoleonic administrators encountered in their quest to establish and legitimize French imperium in conquered territories. The dualities at the basis of the Napoleonic Empire – progress and exploitation; emancipation and occupation; national liberation and occupation – have been the object of previous studies. The contributions brought together in this edited collection build on recent historiographical work to explore in depth the dynamics such dualities generated on the ground in different regions of the empire. Doina Pasca Harsanyi is Professor of History at Central Michigan University, USA. Alexander Mikaberidze is Professor of History at Lousiana State University Shreveport, USA.